Study Design and Rationale of a Randomized Trial Comparing Aspirin–Sarpogrelate Combination Therapy with Aspirin Monotherapy: Effects on Blood Viscosity and Microcirculation in Cardiovascular Patients - Yuran Ahn; Jaehyuk Jang; Seonghyeon Bu; Nay Aung; Hyo-Suk Ahn; Keun-Sang Yum (Diagnostics)
Coronary artery disease (CAD) and peripheral artery disease (PAD) are associated with increased blood viscosity, which contributes to vascular inflammation and impaired microcirculation. Blood viscosity plays a crucial role in disease progression, influencing endothelial function and tissue perfusion. Sarpogrelate hydrochloride, a serotonin receptor antagonist, has antiplatelet and vasodilatory properties that may improve microvascular function and blood rheology. This randomized, parallel-group, open-label, single-center, phase IV clinical trial enrolled 68 patients with both CAD and PAD. The participants were randomized in a 1:1 ratio to receive either aspirin monotherapy (100 mg) or aspirin (100 mg) plus sarpogrelate (300 mg) for 12 weeks. The primary outcome was the change in blood viscosity from baseline to week 12, assessed using the scanning capillary technique. Secondary outcomes included erythrocyte deformability, flow-mediated dilation (FMD), and tissue oxygen delivery index (tODI), which collectively provide insights into microvascular function and oxygen transport efficiency. Elevated blood viscosity is a key factor in cardiovascular disease progression, yet conventional antiplatelet therapy has shown limited effects on hemorheology. Sarpogrelate, by targeting serotonin-mediated pathways, may enhance microcirculatory function and optimize vascular health. These effects could lead to better oxygen delivery and overall vascular health, thereby optimizing cardiovascular outcomes. By integrating hemorheological and vascular markers, this study aims to provide evidence on the potential benefits of combination therapy. Findings could inform optimized antiplatelet strategies to improve vascular health and reduce cardiovascular risk in patients with CAD and PAD.